Cytotoxic alkaloids from the twigs and leaves of Cephalotaxus sinensis. Issue 1 (6th December 2022) - Zhang, Fuxin; Yang, Tao; Yang, Kailing; Zhou, Ruixi; Zhang, Yu; Chen, Wenwen; Liu, Zhetong; Zhan, Guanqun; Guo, Zengjun
Abstract : Twelve new Cephalotaxus alkaloids with cytotoxic activities from the twigs and leaves of Cephalotaxus sinensis . Abstract : Twelve new Cephalotaxus alkaloids (1–12 ) and nine known analogues (13–21 ) were isolated and identified from the twigs and leaves of Cephalotaxus sinensis. The structures of the new compounds (1–12 ) were elucidated by extensive spectroscopic analysis and single-crystal X-ray diffraction analysis. Cephalosine H (8 ) is the third example of an alkaloid containing the cephalolancine skeleton. Cephalosines J and K (10 and 11 ) are the rare natural Δ(2)1-alkene-6-hydroxyl homoerythrina-type alkaloids isolated from the Cephalotaxus genus. The racemization of cephalotaxine-type alkaloids is discussed. Alkaloids 6, 7, 11, 16, 18 and 19 exhibited broad and potent cytotoxicities against five human cancer cell lines, with IC50 values ranging from 0.053 to 10.720 μM, highlighting these compounds as promising leads for the development of new antitumor agents.